The new social contract: 10 suggestions for change. - Vega, Gina; Lacey, James W. (Social Policy)
The writers discuss suggestions for a new social contract between employers and workers. They discuss how the leading buzzwords in American business for the past decade—teamwork and reengineering—reflect changes in the relationships between employers and workers and they point out that the current generation of workers has been led to believe that the tacit contract between employer and employee of previous decades has been broken. They state that if a contract—whereby if employees attended work, did their job adequately, and did not create difficulties the company would provide fair pay, benefits, and job securiy—ever existed, it has long ago been brushed aside by employers as untenable and unnecessary. They contend that forming ideas for action on a new contract requires an understanding of markets, power, and technological change, which are the forces that drive an economy. They suggest that improving the new social contract requires change in expectations, the legal framework, union strategy, and individual initiative. They outline ten ways to bring about this improvement.